The Seroprevalence of Hand-Foot-Mouth Disease in Preschool Children - Cinar, Esma Merve; Kosecik, Mustafa; Aslan, Ferhat Gurkan; Buyukavcı, Mustafa; Koroglu, Mehmet; Elmas, Bahri; Altındis, Mustafa (Journal of Pediatric Infectious Diseases, 2019)
Hand-foot-mouth disease (HFMD) is a systemic and mostly uncomplicated infectious disease caused by the virus of the enterovirus family and manifests as skin and mucosal lesions. Enterovirus 71 (EV71) and coxsackievirus A16 (CA16) are the most commonly detected infectious agents. It is generally observed in children under 5 years of age. In this study, our objective was to determine the seroprevalence of HFMD in preschool children in Sakarya region. A total of 380 children between 1 and 6 years of age were included in the study. Sociodemographic information, clinical findings, and possible risk factors were recorded on a data collection form. Later, serum anti-EV71 and anti-CA16 IgG (immunoglobulin G) antibodies were measured by ELISA. Amongst the 380 children, EV71 IgG positivity was 57.9% and CA16 IgG antibody positivity was 57.4%. There was no difference in seroprevalence between the genders (p > 0.05). Anti-EV71 and anti-CA16 IgG antibody positivity was significantly higher in children aged 1, 2, 3, and 4 years than in 5-year olds (p < 0.05). Seroprevalence was significantly lower in children of mothers who washed their hands before feeding (p < 0.01). High HFMD seroprevalence (> 50%) was observed in the preschool period in the Sakarya region, especially in children aged 1 to 4 years. To prevent infections for which there is no specific treatment, it is very important that the hygiene rules are complied with; in particular, children and their caregivers should pay attention to hand cleansing. We believe that more seroprevalence studies should be performed from different regions to show the status of the disease in our country.
Keywords: hand-mouth-foot disease; Enterovirus 71; Coxsackievirus A16; seroprevalence